Effects of Spontaneous Abortion upon Women’s Physical and Spiritual Status - Fadhi, sarab; ali, Rabea (Iraqi National Journal of Nursing Specialties, 2015)
Background: Spontaneous abortion means that a pregnancy is lost prior to viability, the loss of a fetus weighing less than 500 g, and the loss of an embryo or fetus at 20 weeks gestation or less (WHO, 2001). Glenville, (2001) has reported that suffering a miscarriage is one of the most devastating things that can happen to a woman, and to her husband. Many women conceive easily and are not emotionally or physically prepared for the shock of losing a baby. Objective: To know effects of spontaneous abortion upon physical status and spiritual beliefs , also find out the association between physical status and spiritual beliefs with study variable (demographic & reproductive). Methodology: A descriptive Analytical study was conducted on Non-probability (purposive sample) of (200) women who have suffering from spontaneous abortion in maternity unit from four hospitals at Baghdad City which include Al-Elwiya maternity teaching hospital, and Baghdad teaching hospital , Al –karckh maternity hospital ,and Al-Yarmook teaching hospital. A questionnaire was used as a tool of data collection for the period of February 3rd 2013 to April 26th 2013 to fulfill with objective of the study and consisted of four parts, including demographic, reproductive characteristics, and physical status and spiritual beliefs. A pilot study was carried out to test the reliability of the questionnaire and content validity was carried out through the 20 experts. Descriptive and inferential statistical analyses were used to analyze the data. Results :The results of the study revealed that (26.5%) of women their age range (25-29) years ,(27.5%) graduated from primary school, (25%) of their husband graduated from college or institute, (80%) of study sample were housewives, (54.5%) of their husband were employee, (48%) of study sample is within low category of socioeconomic status. And about the reproductive information (66%) of women were primi and multi gravida, and (25%) of women having at least previous two delivery, and (52.5%) have previous one abortion, also this study present there is no association between physical status and study variables ,but there is a correlation between spiritual beliefs and socio-demographic characteristics (women and husband educational level, women’s occupation and their socioeconomic status), but there is no association between spiritual beliefs and reproductive data. Recommendations: The study recommends that structured teaching program can be presented to women during pregnancy with history of miscarriage which includes meaning, causes, and prevention of miscarriage. The study recommends that collaborative action can be taken by Ministry of Health to publish awareness between women towards the problem by presenting a booklet or lectures about miscarriage.